DIGITAL MARKETING STRATEGY, MARKETING COMMUNICATION AND PROMOTION OF IPHONE USER PURCHASE INTEREST - Djoko Widagdo; Budi Utami; Dwi Wahyono; Achiruddin Siregar; Triana Agustini (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This research aims to analyze the digital marketing strategy, marketing communication, and promotion on iPhone users' purchasing interest.METHODOLOGY - The research method is a quantitative study with a descriptive approach. The research population is all young iPhone users in Yogyakarta City. The research uses a multiple linear regression analysis model.FINDING - The results of the partial analysis of digital marketing strategies and promotions have a significant positive effect on iPhone users' purchasing interest in Yogyakarta City. Marketing communication has a positive but insignificant effect on iPhone users' purchasing interest. Simultaneous results obtained that digital marketing strategies, marketing communication, and promotions have a significant positive effect on iPhone users' purchasing interest in Yogyakarta City. The results of the Adjusted R Square value were proven to be 42.3% and the remaining 57.7% was explained by other variables such as consumer behavior, product quality, and others.